Effects of S/F doping and Li/Mn site exchange in Li2MnSiO4: A first-principles investigation of the structural, electrochemical and electronic properties. (20th January 2021) - Zheng, Shouhong; Hou, Yuhua; Guo, XiaLei; Huang, Youlin; Li, Wei; Tao, Xiaoma
Highlights: A systematic investigation focused on the effect of S and F dopant and Li/Mn site exchange on the properties of Li2 MnSiO4 . The different Li/Mn sites in Li2 MnSiO3.5 R0.5 (R=O, s and F) systems were calculated in detail. Influence mechanism of doping and Li/Mn site exchange on cyclic stability and electrochemical properties was investigated. Cyclic stability of the structure, electrochemical properties and conductivity can be improved by S and F doping. Abstract: Effects of S and F doping and Li/Mn site exchange on structural, electrochemical and electronic properties of Li2 MnSiO4 cathode materials are systematically studied by the first-principles calculations based on density functional theory within the generalized gradient approximation with Hubbard corrections (GGA+ U ). The calculated results about Modulus ratio B/G and Poisson ratio ν show that Li2 MnSiO3.5 R0.5 (R= S and F) possess excellent mechanical properties. The investigation of Young's modulus E and Debye temperature θ D indicates that the doping of S and F is beneficial to the migration of Li + . In addition, the doping of S and F can reduce the theoretical average deintercalation voltage during delithiation and improve the conductivity of Li2 MnSiO4 . The results also show that the site exchange of Li and Mn can effectively reduce the rate of cells volume change when one Li + is removed in per formula unit for the doped systems. Moreover, the charge compensation is completely provided by O and S ions for the first Li + removal in the S-doped system with Li/Mn site exchange, showing that the appearance of Mn 3+ /Mn 4+ Jahn–Teller effect can be delayed, which is beneficial in improving the cycle stability of the system. Also, F doping can play the similar role in delaying the appearance of Mn 3+ /Mn 4+ Jahn–Teller effect, which is due to extra electrons generated by the substitution of O 2− with F − .